The decreasing of NFκB level in gingival junctional epithelium of rat exposed to Porphyromonas gingivalis with application of 1% curcumin on gingival sulcus - Agung Krismariono (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Periodontal disease is a chronic, multi-factorial disease. Chronic periodontitis is one of the main causes of tooth loss. Chronic periodontitis is usually caused by Porphyromonas gingivalis (P. gingivalis). P. gingivalis can induce NFκB activation resulting in the increasing of periodontal extracellular matrix degradation. Curcumin can inhibit NFκB activation and reduce the severity of periodontal degradation. Purpose: This research was aimed to observe level of NFκB in gingival junctional epithelium of rat exposed to Porphyromonas gingivalis with local administration of curcumin. Methods: Sixteen Wistar rat were divided into two groups. Group 1 (treatment) consisted of eight rat given 2 x 106CFU/ml P. gingivalis and 1% curcumin. Meanwhile, group 2 (control) consisted of eight rat given 2 x 106 CFU/ml P. gingivalis only. GCF samples were collected from gingival sulcus. The samples were biochemically analyzed with ELISA method. Data were then analyzed statistically by using independent t-test (α=0.05). Results: The examination of NFκB level showed that there was significant difference between treatment group and control group (p<0.05). The level of NFκB in the treatment group was significantly lower than the control group. Conclusion: It can be concluded that 1% curcumin application can reduce NFκB level in gingival junctional epithelium of rat exposed to P. gingivalis.